2. Parlament i ewolucja systemu partyjnego w Kirgistanie po 2010 roku .......... 43 (Kirgistan – oblicza transformacji, 2020)
THE PARLIAMENT AND THE EVOLUTION OF THE PARTY SYSTEM IN KYRGYZSTAN AFTER 2010Kyrgyzstan’s new constitution has made the parliament the main center of power. The deputies have gained an unprecedented influence on government policy and the functioning of other state bodies. The subsequent parliamentary elections (2010, 2015) and the dynamics of political life confirm, however, that the political groups operating within the party system of the republic are characterized by a low level of institutionalization and, at the same time, a tendency to orient themselves towards a strong leader.